Larp: jogo e experiência vivida - Santos, Raoni Julian Pablo dos (2020)
This study brings together authors and interdisciplinary content, to understand the practice of a type of game, Larp, as an immersive activity and from the perspective of cultural performances. The importance of this study is due to the lack of scientific material that creates the connections between Larp's studies and performances. For this, the selection and research of references are based on reviews to understand the relationship of thoughts between authors in a dialectical and historical-cultural way. In this way, the work sought to understand Larp as a recreational and artistic practice to fill the shortage of material. Therefore, a bibliographic review constituted by historical and dialectical materialism. The results obtained from these connections were the perception and concepts about emotional phenomena in performance actions. In the final considerations, the chosen path contributed to a critical relationship of how the theories are beyond instrumentalizing the object. In this way, allowing the study to continue advancing through the historical and cultural contexts observed within future perspectives.